Role of Zinc Signaling in the Regulation of Mast Cell-, Basophil-, and T Cell-Mediated Allergic Responses - Keigo Nishida; Ryota Uchida (Journal of Immunology Research)
Zinc is essential for maintaining normal structure and physiological function of cells. Its deficiency causes growth retardation, immunodeficiency, and neuronal degeneration. Zinc homeostasis is tightly regulated by zinc transporters and metallothioneins that control zinc concentration and its distribution in individual cells and contributes to zinc signaling. The intracellular zinc signaling regulates immune reactions. Although many molecules involved in these processes have zinc-binding motifs, the molecular mechanisms and the role of zinc in immune responses have not been elucidated. We and others have demonstrated that zinc signaling plays diverse and specific roles in vivo and in vitro in studies using knockout mice lacking zinc transporter function and metallothionein function. In this review, we discuss the impact of zinc signaling focusing particularly on mast cell-, basophil-, and T cell-mediated inflammatory and allergic responses. We also describe zinc signaling dysregulation as a leading health problem in inflammatory disease and allergy.